KAJIAN STILISTIKA BERORIENTASI DIKSI YANG BERINDIKASI NILAI PENDIDIKAN KARAKTER PROFIL PELAJAR PANCASILA PADA KUMPULAN PUISI BULAN TERTUSUK LALANG KARYA D. ZAWAWI IMRON SEBAGAI ALTERNATIF BAHAN AJAR DI SMK - Marliani, Mila; R. Panca Pertiwi Hidayati; Irfan Rifai (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to describe how D. Zawawi Imron manipulates or utilizes diction that indicates the character education value of the Pancasila Student Profile as well as the effects caused by the use of this diction in the collection of poems Bulan Tertusuk Lalang and used as an alternative for Indonesian teaching material in vocational schools. This research applies a qualitative descriptive method using a stylistic approach. This research uses data from the poetry collection Bulan Tertusuk Lalang by D. Zawawi Imron and Indonesian language teaching materials at vocational schools. Data collection was carried out using library study techniques. The results of this research are, D. Zawawi Imron manipulates or utilizes language in ways, namely: (1) using words that contain denotational and connotative meanings through expressions (2) using word data with the Pancasila Student Profile as an indirect way of expressing reality. The effect of D. Zawawi Imron's use of diction in the collection of poems Bulan Tertusuk Lalang is that readers can find out the meaning and message of the collection of the poems as well as provide characteristics of the language used by D. Zawawi Imron. As an alternative Indonesian language teaching material in vocational schools because it meets the requirements and criteria for good teaching material or materials. Interestingly, apart from the meaning of connotation and denotation, in these poems we also find archaic diction (ancient words that are no longer commonly used).One of the functions of this archaic diction is as a means of generating visual images for readers and the value of character education with the Pancasila Student Profile. Apart from that, you can also find understanding related to the holy book Al-Quran, stories of the prophet, history of the Majapahit kingdom, and philosophical theories. The results of data analysis also show that this stylistic study can be used as teaching material for Indonesian language and literature in module form.